Are Homophones Acoustically Distinguished in Child-Directed Speech?. Issue 3 (3rd July 2017) - Conwell, Erin
ABSTRACT: Many approaches to early word learning posit that children assume a one-to-one mapping of form and meaning. However, children's early vocabularies contain homophones, words that violate that assumption. Children might learn such words by exploiting prosodic differences between homophone meanings that are associated with lemma frequency (Gahl, 2008). Such differences have not yet been documented in children's natural language experience and the exaggerated prosody of child-directed speech could either mask the subtle distinctions reported in adult-directed speech or enhance them. This study measured the duration, vowel characteristics, and pitch information of homophone tokens taken from a corpus of child-directed speech. The results show that homophone meanings are acoustically distinct in child-directed speech as a function of lemma frequency, particularly in utterance-final positions. Such distinctions may allow children to maintain separate phonetic representations of homophones until their cognitive and linguistic abilities are robust to violations of the one-to-one bias.